Identifikasi Masalah Dan Potensi Desa Jarak Dalam Upaya Menjadikan Desa Jarak Sebagai Desa Wisata di Kabupaten Jombang - Damayanti, Affiva Lindi; Rusdianto, R Yuniardi (CV. ITTC INDONESIA, 2023)
Jarak Village is one of the villages in Wonosalam District, Jombang Regency. Jarak Village has the potential to become a Tourism Village because it has one of the aspects needed to become a Tourism Village namely the authenticity of its culture, customs, and natural tourism potentials. However, based on surveys and observations from researchers, Jarak Village still has problems or obstacles in developing it into a Tourism Village. Therefore, the purpose of this research is to plan strategies that can be applied to make the Jarak Village feasible to become a Tourism Village in Wonosalam District, Jombang Regency. In this study a qualitative descriptive method was used to get a complete picture of the village of the Distance. The data used is from primary and secondary data obtained through surveys, observations, interviews, documentation, as well as literature studies from previous related studies. The data that has been collected is processed and analyzed using a SWOT study to produce a strategic direction to develop the Distance Village into a Tourism Village. The results of this study are that there are several strategies and detailed descriptions that can be applied, namely in the form of competitive strategies, diversification strategies, overview strategies, and defensive strategies.